(untitled) (Research, Society and Development, 2021)
Polysulfone is a promising material for membrane production. However, aiming to promote greater resistance to scale formation and improvements in permeability, selectivity and resistance (mechanical and chemical) to these types of membranes, the addition of inorganic nanoparticles such as titanium dioxide has been proposed to obtain desired properties and favor applications. The development of polysulfone nanocomposite membranes will make it possible to find a relationship between low cost and high level of performance, due to the use of a smaller amount of inorganic filler introduced in the polymeric material, which may result in synergy between the individual properties of these components, enhancing the performance of this hybrid material obtained. Therefore, this fact demonstrates the importance of obtaining these membranes to improve their properties and, consequently, obtain greater efficiency in PSM for application in microfiltration systems, representing an important contribution to academia and society, in addition to serving as support for work futures. Nevertheless, this work aims to carry out a literature review on microporous membranes made from polysulfone with the introduction of inorganic charges through the phase inversion technique, aiming at its application in the treatment of effluents from the textile industry.